In vitro evaluation of the hepatic lipid accumulation of bisphenol analogs: A high-content screening assay. (October 2020) - Liu, Qian; Shao, Wentao; Weng, Zhenkun; Zhang, Xin; Ding, Guipeng; Xu, Cheng; Xu, Jin; Jiang, Zhaoyan; Gu, Aihua
Abstract: Bisphenol A (BPA) has a variety of adverse effects on human health; therefore, BPA analogs are increasingly used as replacements. Notably, recent studies have revealed that BPA exposure induced hepatic lipid accumulation, but few studies are available regarding the similar effects of other bisphenol analogues (BPs). Thus, in the present study, a high-content screening (HCS) assay was performed to simultaneously evaluate the hepatic lipid accumulation of 13 BPs in vitro . The BPs induced lipid deposition in HepG2 cells ranking as below: 4, 4′-thiodiphenol (TDP) < bisphenol S (BPS) < 4, 4′-dihydroxybenzophenone (DHBP) < tetrabromobisphenol A (TBBPA) < tetrachlorobisphenol A (TCBPA) < bisphenol E (BPE) < bisphenol F (BPF) < bisphenol B (BPB) < bisphenol AF (BPAF) < bisphenol A (BPA) < bisphenol C (BPC) < tetramethylbisphenol A (TMBPA) < bisphenol AP (BPAP). Meanwhile, Oil Red O staining and triacylglycerol detection further validated the lipid accumulation elicited by the latter 8 BPs, which exhibited the more significant effects on lipid deposition. Mechanistically, significantly increased expressions of genes involved in fatty acid synthesis and nuclear receptors and decreased levels of genes associated with fatty acid β-oxidation were observed under BPs treatment. Therefore, the present work is the first to systematically provide direct evidence for BPs-induced hepatic lipid accumulation in vitro via HCS, which can be helpful for safety assessments of BPs. Highlights: A high-content screening assay was performed to evaluate the hepatic lipid accumulation of 13 bisphenols in vitro . BPE, BPF, BPB, BPAF, BPA, BPC, TMBPA, and BPAP exhibited the significant effects on lipid deposition. BPAP, BPA, and BPAF significantly regulated genes involved in lipid β-oxidation, lipogenesis and nuclear receptor genes.